(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
This study aimed to reduce the university-industry gap from the perspective of leadership and entrepreneurship. The focus of this research is to assess the influence of transformational leadership of manager on academic staff’s entrepreneurial orientation and to pave the way for identifying potential opportunities, generating new ideas in industrial relation, and to subsequently narrow the university-industry problem. In order to understand the contribution of leadership within the university–industry context, this research reviewed the effect of transformational leadership style on entrepreneurial orientation and then examined the existing relationship. The population of this study is the academic staff of a public university in Iran. A research sample of 295 academic staff was chosen by using stratified sampling technique. Technical analysis of data applied Structural Equation Modeling in two step: measurement model for testing the construct validity of questionnaires and structural model for hypothesizes testing with mathematical program. The results showed that transformational leadership was the best predictor for entrepreneurial orientation. The research findings in this study revealed that the quality of transformational leadership within an organization had an effect on the entrepreneurial orientation. One of the managerial implications of this study is to reinforce the recognition and basis of enhancing entrepreneurial orientation by transformational leadership.